Well-Posedness of a Nonlocal Stage-Structured Population Model with Free Boundary (Journal of Mathematical Study, 2024)
We propose a delay-induced nonlocal free boundary problem by modelingthe invasion of a two-stage structured species, where the nonlocal interaction is causedjointly by time delay, free boundary and the diffusion. After establishing a comparisonprinciple and a priori boundedness estimates, we prove the local and global existenceof classical solutions for the model.
Keywords: Reaction-diffusion equation; free boundary; time delay.